Ultrasound Molecular Imaging With BR55, a Predictive Tool of Antiangiogenic Treatment Efficacy in a Chemo-Induced Mammary Tumor Model. Issue 10 (October 2020) - Helbert, Alexandre; Von Wronski, Mathew; Colevret, Delphine; Botteron, Catherine; Padilla, Frederic; Bettinger, Thierry; Tardy, Isabelle; Hyvelin, Jean-Marc
Abstract : Objectives: The aim of this study was to evaluate the added value of ultrasound molecular imaging of the vascular growth factor receptor 2 (VEGFR2) expression, using the clinical grade contrast agent BR55, for the early evaluation of antiangiogenic treatment efficacy in a chemo-induced rat mammary tumor model. Materials and Methods: In this preclinical study, chemo-induced rat mammary tumors were obtained after a single injection of N -nitroso- N -methylurea intraperitoneally in 46 prepubescent (age 38 ± 2 days) female rats. All experiments were performed under the authorization of the Direction Générale de la Santé, Geneva, Switzerland. Once tumor reached 0.8 cm in the largest cross-section, animals were enrolled in a sunitinib- or vehicle-treated group. Ultrasound molecular imaging was performed using BR55, a clinical grade targeted contrast agent against VEGFR2, before therapy and up to 72 hours. Anatomical changes of tumor over time, that is, area of the tumor largest cross-section and tumor volume, were measured in B-mode. Signal from microbubbles was detected in a nonlinear contrast mode (power modulation) using the iU22 diagnostic ultrasound system (Phillips, United States) equipped with a L12–5 linear transducer (transmit frequency 5 MHz). Peak enhancement and wash-in area under the curve were extracted from the time intensity curves generated by a dedicated quantification software for contrast ultrasound, so-called VueBox (Bracco Suisse SA, Switzerland). The signal of bound BR55 microbubbles in the tumor was quantified 10 minutes after injection. Altogether, these parameters were used to monitor tumoral response to treatment at the anatomical, functional, and molecular levels. At each time point, a cohort of tumors was harvested for the assessment of CD31 and VEGFR2 expression by immunohistochemistry staining. Results: Under sunitinib therapy, assessment of the expression of VEGFR2 by ultrasound molecular imaging with BR55 reveals a significant difference as early as 12 hours after first dosing (−25%), whereas tumor size significant change occurs only after 24 hours. At the end of the therapeutic protocol, 72 hours after the onset of treatment, molecular changes are more marked with a 80% decrease compared with only 40% for the anatomic parameters. Ultrasound molecular imaging observations suggesting a decrease in VEGFR2 expression in treated tumors were corroborated by semiquantitative grading of VEGFR2, showing a decrease expression over time. Functional parameters measured in the perfusion phase also show a decrease along treatment, significant for 24 hours and of 48% of peak enhancement at the end of protocol. Conclusions: Anatomical, functional, and molecular evaluations are feasible in a single examination using BR55 ultrasound targeted contrast agent. Ultrasound molecular imaging of VEGFR2 can depict an early response to antiangiogenic treatment in a rat mammary tumor model. This imaging modality has a potential for early assessment of each patient's response, which could be useful to take decisions on therapeutic protocol, providing as such an imaging tool for personalized medicine.